Akuntabilitas Pengelolaan Alokasi Dana Desa - Mais, Rimi Gusliana; Nuryati, Tutty; Handoko Sakti, Sri; Lestari, Lestari (Universitas Muhammadiyah Jakarta, 2024)
Objectives: This study aims to evaluate the village government's role in effectively managing Village Fund Allocations in Gadung Village, particularly during the planning, implementation, administration, reporting, and accountability stages in adherence to the Minister of Home Affairs Regulation Number 20 of 2018.Design/Method/Approach: Employing qualitative methods such as interviews, observation, and documentation, this research elucidates how the village government handles the allocation of village funds in Gadung Village. The study was conducted at the Gadung Village office.Results/Findings: The findings indicate that the village government demonstrates accountability across all stages of planning, implementation, administration, reporting, and accountability in managing the Village Fund Allocation (VFA) in Gadung Village. The planning stage utilizes Musrenbangdes as a mechanism to ensure accountability. The implementation stage adheres to regulatory mechanisms, while the administration stage showcases accountable management through meticulous bookkeeping and reports. The reporting and accountability stages follow a guided report format to ensure transparency.Theoretical contribution: This study contributes to the enhancement of knowledge and awareness regarding the crucial role of accountability in reporting the use of VFA.Practical contribution: The utilization of VFA report of the Bangka Village requires continuous monitoring at each implementation stage, particularly in administration, to ensure compliance with regulations and prevent legal discrepancies, thereby fostering increased trust in ADD in the future.Limitations: This study specifically explores village financial management as outlined in the Minister of Home Affairs Regulation Number 20 of 2018, encompassing planning, implementation, administration, reporting, and accountability. However, a comprehensive review of each component of VFA financial management and a detailed analysis of nominal village finances have not been undertaken